Permodelan Genangan Banjir Rob Sungai Dumai Menggunakan HEC - RAS 2D - Ramadhan, Rahmat; Putra, Sony Adiya; Halimatusadiyah (SLUMP TeS : Jurnal Teknik Sipil, 2024)
The existence of climate change and global warming has led to increased public awareness in Indonesia of the impact of these problems, especially people who live in coastal areas. Dumai is one of the cities located on the coast, therefore the purpose of this study was to determine the extent of the ROB flood overflow with the HEC-RAS program and the impact that occurred in the city of Dumai when the ROB floods came. From the modeling carried out in February 2023 and the results of a community survey, it was found that are of ROB flood runoff on February 10, 19 and 21 obtained the area of runo 250,418,12 m2, 234,738,94 m2, 272,905,31 m2 and the survey results in settlements of 15 people, the following results were obtained: 7 people answered that their facilities and infrastructure were damaged due to ROB floods, 2 people answered erosion and landslides, and 6 other people answered that the environment around their house was polluted.